Pengaruh Manajemen Laba, Ukuran Perusahaan, Likuiditas, dan Profitabilitas terhadap Agresivitas Pajak - Bagas Krisnugraha; Trisnawati Rahayu; YP Supardiyono (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2021)
This study aims to determine the effect of earnings management, firm size, liquidity, and profitability on tax aggressiveness. Earnings management is measured using discretionary accruals (DA), company size is proxied by the natural logarithm (Ln) of total assets, liquidity is proxied by current ratio, profitability is proxied by return on assets (ROA), and tax aggressiveness is proxied by effective tax rate (ETR). The type of research used is quantitative. The population in this study are property, real estate, and building construction companies listed on the Indonesia Stock Exchange in 2017-2019. The sample selection method in this study uses judgment sampling which is part of purposive sampling where sampling is based on criteria in the form of certain considerations. The data used in this research is secondary data obtained from the Indonesia Stock Exchange (IDX) and the company's website. The data analysis technique used multiple linear regression analysis method. The results showed that earnings management, firm size, and liquidity had no effect on tax aggressiveness. Profitability has a positive effect on tax aggressiveness.